2016
DOI: 10.1002/cjoc.201600223
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polypyridine Co Complex as an Efficient Catalyst for Photo‐Induced Water Oxidation

Abstract: A novel mononuclear cobalt complex 1 was synthesized by treatment of CoCl 2 •6H 2 O with a COOMe functionalized TPA ligand (TPA=tris(2-pyridylmethyl)amine). In a basic borate buffer, 1 acts as an efficient catalyst for water oxidation, which is confirmed by an extinct catalytic oxidant wave in electrochemistry. Visible light-driven water oxidation has been achieved by 1 with a TON of 127.7 and a TOF of 3.8 s 1 respectively in a homogeneous system. In comparison to the reference RC with naked TPA, the higher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…For example, for the Fe-and Co-based mononuclear WOCs 6, 11, and 12, it was concluded that substituents with higher electronegativity favored higher catalytic activity. [74][75][76] Instead, this positive promotion was supported with electron-donating ligands for Ni-based mononuclear WOC 15, 77 which is consistent with the observations for the axial ligand R (R designates pyridine and its derivatives) on WOC 9. 52 Nevertheless, it has been widely proposed that the activity promotion originates from a lower energy barrier for O-O bond formation.…”
Section: Chem Soc Rev Review Articlesupporting
confidence: 76%
“…For example, for the Fe-and Co-based mononuclear WOCs 6, 11, and 12, it was concluded that substituents with higher electronegativity favored higher catalytic activity. [74][75][76] Instead, this positive promotion was supported with electron-donating ligands for Ni-based mononuclear WOC 15, 77 which is consistent with the observations for the axial ligand R (R designates pyridine and its derivatives) on WOC 9. 52 Nevertheless, it has been widely proposed that the activity promotion originates from a lower energy barrier for O-O bond formation.…”
Section: Chem Soc Rev Review Articlesupporting
confidence: 76%
“…Complex 105, [Co(PY5OH)(Cl)] + , was inspired by studies of complex 104 and features free hydroxy groups (in lieu of methoxy), which allows for further functionalization [175,176]. [179]. In comparison, complex 107 with non-functionalized TPA showed reduced activity by roughly an order of magnitude (TON of 12.6 and TOF 0.3 s −1 ); the high efficiency of complex 106 was attributed to the moderately more electron-withdrawing nature of COOMefunctionalized TPA (or steric considerations), thought to increase the stability of 106 by precluding self-oxidation and dimerization [179].…”
Section: −O]mentioning
confidence: 99%
“…[179]. In comparison, complex 107 with non-functionalized TPA showed reduced activity by roughly an order of magnitude (TON of 12.6 and TOF 0.3 s −1 ); the high efficiency of complex 106 was attributed to the moderately more electron-withdrawing nature of COOMefunctionalized TPA (or steric considerations), thought to increase the stability of 106 by precluding self-oxidation and dimerization [179]. Interestingly, both complexes 106 and 107 have chloride ligands, which enhanced the catalytic activity relative to complex 104.…”
Section: −O]mentioning
confidence: 99%